Glossanodon macrocephalus, a new argentine fish (Argentinidae) from the Arabian Sea - Bineesh, Kinattumkara; Nashad, Musaliyarakam; Kumar, K.v. Aneesh; Endo, Hiromitsu (Zootaxa, 2019)
A new species of argentinid fish, Glossanodon macrocephalus Bineesh & Endo, from the Arabian Sea, off the southwestern coast of India, is described on the basis of four specimens (129–164 mm SL). The new species clearly differs from its congeners in the following combination of characters: dorsal-fin rays 10–11; pectoral-fin rays 21–23; anal-fin rays 12–13; pelvic-fin rays 11–12; branchiostegal rays 5; gill rakers on first arch 30–36; vertebrae 47–48; a patch of small conical teeth on middle of lower jaws; predorsal 49–51% SL; prepectoral 36–39% SL; prepelvic 57–58% SL; distance from pelvic to anal-fin origin 26–28% SL; head length 35–39% SL; eye diameter 22–26% HL; snout length 28–30% HL; location of anus immediately anterior to anal-fin origin; broad longitudinal black stripe above lateral line; dark spot on the base to half of pectoral fin; and no teeth on tongue. The new species is a benthopelagic dweller on muddy bottoms in depths of around 300–600 m.